Question
upstudy study bank question image url

11) \( -2 \sqrt{12}-\sqrt{12} \)

Ask by Lowe Cox. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The simplified result is \( -6\sqrt{3} \).

Solution

We start with the expression:   -2√12 - √12 Step 1: Combine the like terms (the radical part √12 is common):   -2√12 - 1√12 = -(2 + 1)√12 = -3√12 Step 2: Simplify √12:   √12 = √(4 × 3) = √4 · √3 = 2√3 Step 3: Substitute back:   -3√12 = -3(2√3) = -6√3 Thus, the simplified result is:   -6√3

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To simplify \( -2 \sqrt{12} - \sqrt{12} \), first, note that both terms contain the same radical, \( \sqrt{12} \). You can combine them as follows: \[ -2\sqrt{12} - 1\sqrt{12} = (-2 - 1)\sqrt{12} = -3\sqrt{12}. \] Next, simplify \( \sqrt{12} \). Since \( 12 = 4 \times 3 \), we have \( \sqrt{12} = \sqrt{4 \times 3} = 2\sqrt{3} \). Substituting this back into the expression gives: \[ -3\sqrt{12} = -3(2\sqrt{3}) = -6\sqrt{3}. \] So, the final simplified form is \( -6\sqrt{3} \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy